The sing-song of old man kangaroo - Cary, Gemma; Jarzabek, Ela; Kipling, Rudyard (Manila : WS Pacific Publications, 2020)
Relates how the proud kangaroo became different from all other animals.
"Retold from the Rudyard Kipling original"
Keywords: Kangaroos -- Juvenile fiction